Relationship Between Knowledge and Perception with HIV/AIDS Prevention Efforts in Key Populations - Siti Latipah; Naryati Naryati (Poltekkes Kemenkes Surakarta, 2025)
Background: HIV transmission often occurs through unsafe sex, particularly with sex workers, making key populations crucial in the spread of HIV/AIDS. One key strategy to reduce HIV/AIDS morbidity and mortality is implementing prevention programs targeting at-risk groups. The study aims to examine the relationship between knowledge and perception and HIV/AIDS prevention efforts among key populations in Tangerang City. Method: Quantitative with cross-sectional analytical correlation. A sample of 69 people was conducted by snowball technic sampling. This study used the HIV-KQ-18, HIV perceptions statements referring to the six components of the Health Belief Model theory and Behavioral Surveillance Survey (BSS). Data analysis was performed using the Chi-Square Test of Independence to assess the relationship between knowledge level, perception level. Results: respondent characteristics Age ≥ 21 years 59.4%, high school education 69.7%, length of work ≥ 3 years 59.3%. Relationship between knowledge level and HIV/AIDS prevention efforts: p-value 0.002. Relationship between perception level and HIV/AIDS prevention efforts: p-value 0.002. Relationship between knowledge and perception and HIV/AIDS prevention efforts: p-value < 0.001. Conclusion: The study found that knowledge and perception significantly influence HIV/AIDS prevention among female sex workers. However, consistent prevention is hindered by personal, social, and structural barriers, including negotiation difficulties, economic dependence, stigma, and limited-service access. Effective interventions must be comprehensive, combining knowledge improvement with skills training, stigma reduction, barrier removal, and supportive policies.